2022
DOI: 10.1002/pca.3188
|View full text |Cite
|
Sign up to set email alerts
|

A reliable quantitative method for determining CBD content and release from transdermal patches in Franz cells

Abstract: Introduction: There are several cannabidiol (CBD) transdermal patches available on the market. However, none are FDA-approved. Furthermore, not much evidence has been published about CBD release and skin permeation from such patches, so the effectiveness and reliability remain unclear.Objectives: We aimed to develop a method to determine the in vitro release and skin permeation of CBD from transdermal patches using Franz cell diffusion in combination with quantitative 1 H-NMR (qNMR). Materials and Methods:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The skin permeation ability used Strat-M™ membrane with a transdermal diffusion system (DHC-6T, LOGAN Inc, USA). 1 , 49 Thus, 10 mg CBD and CTD containing the same weight CBD were added on the top of the Strat-M™ membrane. The diffusion experiment was initiated by charging the receiver compartment containing 6%wt Tween 80 in PBS for all groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin permeation ability used Strat-M™ membrane with a transdermal diffusion system (DHC-6T, LOGAN Inc, USA). 1 , 49 Thus, 10 mg CBD and CTD containing the same weight CBD were added on the top of the Strat-M™ membrane. The diffusion experiment was initiated by charging the receiver compartment containing 6%wt Tween 80 in PBS for all groups.…”
Section: Methodsmentioning
confidence: 99%
“…Cannabidiol (CBD) is a promising therapeutic drug with low addictive potential and a favorable safety profile. 1 Studies have shown that CBD does not exhibit the psychoactive effects commonly associated with tetrahydrocannabinol (THC), making it a safer option for therapeutic use. Its non-addictive nature makes it an appealing choice for patients seeking effective treatments without the risk of dependency.…”
Section: Introductionmentioning
confidence: 99%
“…Franz-type diffusion cells (LGA, Berkeley, CA, USA) were used to assess BMTZ release from the emulsions under investigation [53][54][55][56]. Experiments were performed using cellulose membranes previously moistened by immersion in distilled water for 1 hour at room temperature.…”
Section: In Vitro Release Of Bemotrizinolmentioning
confidence: 99%
“…As time prolongs, the active ingredient's release slows down due to an increased diffusion distance for the active ingredient. 32 Diffusion is the main drug release mechanism in the Higuchi model. 33 In Vitro Penetration Study of Patch Considering the results of the physical attributes, Formula 1 was selected as the best formula for the ensuing penetration test.…”
Section: Surface Morphology Test Of Patchmentioning
confidence: 99%